An analysis of factors affecting mobile banking adoption. Issue 2 (18th July 2019) - Elhajjar, Samer; Ouaida, Fadila
Abstract : Purpose: The purpose of this paper is to develop a conceptual model that explains the most important factors affecting mobile banking adoption for Lebanese banking customers. Design/methodology/approach: Based on the data collected through a survey, structural equations modeling and path analysis were utilized to test the hypotheses. In total, 320 questionnaires were collected from Lebanese customers. Findings: The results show that digital literacy, resistance to change, perceived risk, perceived ease of use, and perceived usefulness were found to be the main variables affecting users' attitudes toward adoption of mobile banking, whereas awareness and compatibility showed no significant impact on adoption. In addition, both subjective norms and personal innovativeness influenced users' adoption moderated the relationships between usefulness attitude and ease of use attitude. Originality/value: The study fills a gap in the literature by exploring e-readiness influence on adoption through testing the variable "digital literacy" and by examining the effect of the frequency of branch visits on the intention to adopt mobile banking. Social and individual variables, such as social influence and personal innovativeness, which were rarely examined in past studies, are employed in this research. All of our respondents were actual bank account holders.